SATISFACTION LEVEL OF SAMSAT LINK USERS AND RELATIONSHIP WITH MOTOR VEHICLE TAX REPORTS AT SAMSAT GORONTALO - Djamaluddin, Musdalifah; Masjrul Janto Usman; Muten S. Nuna; Tabo, Sarfan (Gema Kampus IISIP YAPIS Biak, 2026)
The digitalization of public services in the tax sector, particularly through the Link Samsat innovation in Gorontalo Province, aims to improve the convenience, efficiency, and compliance of motor vehicle taxpayers. However, the implementation of this system still faces various obstacles, such as low public understanding, technical issues, and low adoption rates that impact tax reporting compliance. This study aims to analyze the level of satisfaction of Link Samsat users and its relationship with compliance of motor vehicle tax reporting at the Gorontalo Samsat, as well as to identify the factors that influence it. The study used a qualitative approach with a case study type. Data collection was conducted through observation, interviews, documentation, and literature review, with informants consisting of Samsat officers and taxpayers. Data analysis used an interactive model that includes data reduction, data presentation, and drawing conclusions. The results show that the level of satisfaction of Link Samsat users is influenced by product or service quality, service quality, and security quality. This service is considered effective and efficient because it can speed up the tax payment process and reduce queues. However, the main obstacles include a lack of socialization, network limitations, and the lack of integration of services between regions. User satisfaction has been shown to contribute to increased tax compliance, although not optimally. Therefore, improving the quality of services, wider socialization, and improving the technical system are needed to optimize the use of this service and increase compliance of motor vehicle taxpayers.